Association of TCF7L2 Gene Polymorphism With Non Obesetype 2 Diabetes Mellitus in Javanese Population - Yuniastuti, Ari; Susanti, R; Nugrahaningsih, Nugrahaningsih; R, Rahmatika Saputri (Universitas PGRI Semarang, 2023)
Type 2 diabetes is characterized by insulin deficiency due to inadequate insulin secretion or decreased tissue response to insulin at one or more points. Three important factors that influence the pathogenesis of type 2 DM are individual factors or ethnic genetics, factors of pancreatic Î² cell damage and insulin resistance factors. The TCF7L2 gene is a gene that codes for TCF7L2 protein, a group of proteins that act as transcription factors in the Wnt signal pathway. TCF7L2 gene polymorphism occurs when cytosine is replaced with thymine in the intron 3 position in wild-type due to alternative splicing.The purpose study was to determine the frequency of TCF7L2 gene polymorphism in Javanese type 2 non-obese DM patients in Semarang. Detection of TCF7L2 gene polymorphism was carried out on 49 people with type 2 non-obese DM patients and 38 people not with type 2 DM using the PCR-RFLP method. The restriction enzyme used is Rsa1. The allele frequency of TCF7L2 gene polymorphism was analyzed by Chi-square and analysis of sample characteristics was carried out with Odds Ratio. The results showed that there were significant differences in the allele frequency of TCF7L2 gene polymorphism and in the characteristics of age, KGD and systole between case subjects and control subjects. From this study it was concluded that TCF7L2 gene polymorphism is associated with the type 2 DM through interactions between genetic factors (T allele) and life style.